Childhood maltreatment is associated with attachment insecurities, dissociation and alexithymia in bipolar disorder. (February 2018) - Kefeli, Mehmet Celal; Turow, Rachel Goldsmith; Yıldırım, Abdullah; Boysan, Murat
Abstract: Child maltreatment is a public health issue that is a well-established risk factor for many psychological conditions, including bipolar disorder. The current study is one of the first to investigate associations among child maltreatment, dissociative symptomatology, alexithymia, anxiety, depression, and attachment insecurities. 40 patients with bipolar disorder-I and 40 healthy subjects matched for age, gender, and education participated in the study. The Dissociative Experiences Scale (DES), Somatoform Dissociation Questionnaire (SDQ), Childhood Trauma Questionnaire (CTQ-28), Toronto Alexithymia Scale (TAS-20), Depression Anxiety Stress Scale (DASS-21), and Experiences in Close Relationships-Revised (ECR-R) were completed by participants. In comparison to control participants, patients with bipolar disorder-I reported significantly more frequent abusive experiences in childhood, higher levels of attachment insecurities, more severe pathological and somatoform dissociation, as well as higher scores on measures of alexithymia, anxiety, depression and psychological stress. Reports of psychopathology among first-degree relatives (OR = 102.169, 95%IC = 4.596–2271.255; P < 0.01 ) and childhood emotional trauma (OR = 1.032; 95%CI = 0.782–1.363, P = 0.05 ) significantly contributed to bipolar disorder-I diagnosis. In contrast, absorption was negatively associated with bipolar illness (OR = 0.852; 95% CI = 0.747–0.973, P < 0.05 ). Our results showed significant associations between childhood trauma exposure and risk of bipolar disorder. Moreover, the results demonstrate that emotional abuse exposure predicts bipolar illness. Highlights: BP had greater dissociation, alexithymia, attachment insecurities and abuse than controls. Familial loading and emotional abuse were associated with development of disorder. Physical neglect, dissociation and depression contributed to frequency of depressive episodes.